A phylogenetic hypothesis for "Helianthemum" ("Cistaceae") in the Iberian Peninsula - Parejo-Farnés, Clara (Botanica Complutensis, 2013)
We have sequenced the nuclear DNA internal transcribed spacer (ITS1+5.8S+ITS2) from samples collected in the field belonging to all taxa ofHelianthemum in the Iberian Peninsula and analysed the data matrix by both Bayesian and Maximum Likelihood approaches. The phylogenetic hypothesis that we present here provides strong support for the monophyly of the genus and for the above-species systematics (sections and subgenera) considered inFlora iberica. Nevertheless, most species and subspecies in sections Helianthemum and Pseudocistusclustered in ample polytomies with poor resolution and branch support. This topology is interpreted to be consequence of frequent events of hybridization and introgression and/or rapid adaptive radiation in the genus Helianthemum, the most diversified lineage within the family Cistaceae.
Keywords: adaptive radiation; Betic-Rifean hot spot; hybridization; Mediterranean flora